2006
DOI: 10.1111/j.1464-410x.2006.06275.x
|View full text |Cite|
|
Sign up to set email alerts
|

Tolerability, efficacy and pharmacokinetics of bicalutamide 300 mg, 450 mg or 600 mg as monotherapy for patients with locally advanced or metastatic prostate cancer, compared with castration

Abstract: OBJECTIVE To evaluate the pharmacokinetics, tolerability and effect on endocrinology of bicalutamide given as once‐daily monotherapy at doses of >150 mg to patients with locally advanced (M0) or metastatic (M1) prostate cancer, with efficacy as a secondary endpoint. PATIENTS AND METHODS Patients were initially enrolled to receive bicalutamide 300 mg in a non‐randomized phase, after which further patients were randomized to higher bicalutamide doses (in 150 mg increments) or castration. Overall, 248 patients re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 20 publications
2
36
0
1
Order By: Relevance
“…The safety and tolerability results obtained in this study are consistent with those expected in a pediatric population of boys with testotoxicosis and with the known safety profiles of bicalutamide and anastrozole [14][15][16][17][18][19][20][21] . For example, the most common treatment-related AE, gynecomastia, is both a feature of the disease as well as a consequence of bicalutamide treatment.…”
Section: Twelve Months Of Treatment Of Patients Withsupporting
confidence: 90%
See 1 more Smart Citation
“…The safety and tolerability results obtained in this study are consistent with those expected in a pediatric population of boys with testotoxicosis and with the known safety profiles of bicalutamide and anastrozole [14][15][16][17][18][19][20][21] . For example, the most common treatment-related AE, gynecomastia, is both a feature of the disease as well as a consequence of bicalutamide treatment.…”
Section: Twelve Months Of Treatment Of Patients Withsupporting
confidence: 90%
“…Since this early study, more potent and specific non-steroidal antiandrogens, such as bicalutamide (Casodex™), and aromatase inhibitors, such as anastrozole (Arimidex™), have become available for the treatment of hormone-sensitive cancers and a number of studies have confirmed the efficacy and favorable tolerability profile of bicalutamide [14][15][16][17] and anastrozole [18][19][20][21] in adults. The most common adverse events (AEs) reported with bicalutamide are gynecomastia and breast pain, while anastrozole is associated with an increased risk of bone fracture compared with tamoxifen during long-term use in post-menopausal women.…”
mentioning
confidence: 99%
“…This study demonstrates that Hsp90 inhibitors act in synergy with AR antagonists to enhance AR blockade and reduce survival of prostate cancer cells while also minimizing known mechanisms of resistance. Importantly, these effects were demonstrated using doses of each agent that individually were not effective and are both clinically achievable and tolerable (Kelly et al 2003, Tyrrell et al 2006, Solit et al 2007.…”
Section: Discussionmentioning
confidence: 99%
“…In nonmetastatic patients, reported results are not considered sufficiently mature at this time, whereas a significant survival advantage for castration was seen in the M1 subgroup [71]. More recently, Tyrrell et al [72] studied higher-dose bicalutamide (300, 450, and 600 mg) with regard to tolerability, pharmacokinetics, and clinical efficacy in M0 and M1 patients. Although survival resulted comparable to that for men receiving castration, larger series of patients are needed to confirm these data.…”
Section: Evidence Synthesismentioning
confidence: 99%